Comprehensive In Silico Analysis and Transcriptional Profiles Highlight the Importance of Mitochondrial Dicarboxylate Carriers (DICs) on Hypoxia Response in Both Arabidopsis thaliana and Eucalyptus grandis - Barreto, Pedro [UNESP]; Arcuri, Mariana L. C. [UNESP]; Lima, Rômulo Pedro Macêdo [UNESP]; Marino, Celso Luis [UNESP]; Maia, Ivan G. [UNESP] (My University, 2022)
Plant dicarboxylate carriers (DICs) transport a wide range of dicarboxylates across the mitochondrial inner membrane. The Arabidopsis thaliana DIC family is composed of three genes (AtDIC1, 2 and 3), whereas two genes (EgDIC1 and EgDIC2) have been retrieved in Eucalyptus grandis. Here, by combining in silico and in planta analyses, we provide evidence that DICs are partially redundant, important in plant adaptation to environmental stresses and part of a low-oxygen response in both species. AtDIC1 and AtDIC2 are present in most plant species and have very similar gene structure, developmental expression patterns and absolute expression across natural Arabidopsis accessions. In contrast, AtDIC3 seems to be an early genome acquisition found in Brassicaceae and shows relatively low (or no) expression across these accessions. In silico analysis revealed that both AtDICs and EgDICs are highly responsive to stresses, especially to cold and submergence, while their promoters are enriched for stress-responsive transcription factors binding sites. The expression of AtDIC1 and AtDIC2 is highly correlated across natural accessions and in response to stresses, while no correlation was found for AtDIC3. Gene ontology enrichment analysis suggests a role for AtDIC1 and AtDIC2 in response to hypoxia, and for AtDIC3 in phosphate starvation. Accordingly, the investigated genes are induced by submergence stress in A. thaliana and E. grandis while AtDIC2 overexpression improved seedling survival to submergence. Interestingly, the induction of AtDIC1 and AtDIC2 is abrogated in the erfVII mutant that is devoid of plant oxygen sensing, suggesting that these genes are part of a conserved hypoxia response in Arabidopsis.
Keywords: Abiotic stress; DIC; Dicarboxylates; Hypoxia; Mitochondria; Submergence